Protein restriction associated with high fat induces metabolic dysregulation without obesity in juvenile mice - Amélie Joly; Jean-Louis Thoumas; Anne Lambert; Estelle Caillon; François Leulier; Filipe De Vadder (Nutrition & Metabolism)
Abstract Dysregulation of energy metabolism, including hyperglycemia, insulin resistance and fatty liver have been reported in a substantial proportion of lean children. However, non-obese murine models recapitulating these features are lacking to study the mechanisms underlying the development of metabolic dysregulations in lean children. Here, we develop a model of diet-induced metabolic dysfunction without obesity in juvenile mice by feeding male and female mice a diet reflecting Western nutritional intake combined with protein restriction (mWD) during 5 weeks after weaning. mWD-fed mice (35% fat, 8% protein) do not exhibit significant weight gain and have moderate increase in adiposity compared to control mice (16% fat, 20% protein). After 3 weeks of mWD, juvenile mice have impaired glucose metabolism including hyperglycemia, insulin resistance and glucose intolerance. mWD also triggers hepatic metabolism alterations, as shown by the development of simple liver steatosis. Both male and female mice fed with mWD displayed metabolic dysregulation, which a probiotic treatment with Lactiplantibacillus plantarum WJL failed to improve. Overall, mWD-fed mice appear to be a good preclinical model to study the development of diet-induced metabolic dysfunction without obesity in juveniles.